Langerhans cells from women with cervical precancerous lesions become functionally responsive against human papillomavirus after activation with stabilized Poly-I:C - DA SILVA, Diane M. (Clin Immunol, 2015)
Human papillomavirus (HPV)-mediated suppression of Langerhans cell (LC) function can lead to persistent infection and development of cervical intraepithelial neoplasia (CIN). Women with HPV-induced high-grade CIN2/3 have not mounted an effective immune response against HPV, yet it is unknown if LC-mediated T cell activation from such women is functionally impaired against HPV. We investigated the functional activation of in vitro generated LC and their ability to induce HPV16-specific T cells from CIN2/3 patients after exposure to HPV16 followed by treatment with stabilized Poly-I:C (s-Poly-I:C). LC from patients exposed to HPV16 demonstrated a lack of costimulatory molecule expression, inflammatory cytokine secretion, and chemokine-directed migration. Conversely, s-Poly-I:C caused significant phenotypic and functional activation of HPV16-exposed LC, which resulted in de novo generation of HPV16-specific CD8(+) T cells. Our results highlight that LC of women with a history of persistent HPV infection can present HPV antigens and are capable of inducing an adaptive T cell immune response when given the proper stimulus, suggesting s-Poly-I:C compounds may be attractive immunomodulators for LC-mediated clearance of persistent HPV infection.